2013
DOI: 10.4103/2152-7806.113651
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous sinus thrombosis complicated by subdural hematomas: Case series and literature review

Abstract: Background:Cerebral venous sinus thrombosis (CVST) can cause elevated intracranial pressure, hemorrhagic venous infarct, and cortical subarachnoid hemorrhage. We present a case series and literature review to illustrate that CVST can also present with subdural hematoma (SDH).Case Description:Chart review was completed on a retrospective case series of CVST with spontaneous SDH. We also conducted a literature search. Over a 6 year interval, three patients with CVST and SDH were admitted to the neurointensive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Studies show that 11% of all CVTs might be related to malignancy [13]. Nevertheless, CVT has only rarely been associated to SH [14], both of which are usually caused by intracranial hypotension, not fit for our patient presentation. Likewise, isolated SH is a rare presentation of AVM or aneurism [15,16].…”
Section: Discussionmentioning
confidence: 63%
“…Studies show that 11% of all CVTs might be related to malignancy [13]. Nevertheless, CVT has only rarely been associated to SH [14], both of which are usually caused by intracranial hypotension, not fit for our patient presentation. Likewise, isolated SH is a rare presentation of AVM or aneurism [15,16].…”
Section: Discussionmentioning
confidence: 63%
“…It is well known that venous hypertension can cause cortical ischemia and hemorrhage [16]. In 2013 Akins et al [17] reported on 3 cases of cerebral venous sinus thrombosis causing subdural hematoma and found 6 further cases published in the literature. It is possible that the etiology of the cSDH could be slow bleeding from engorged congested cortical veins [17].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013 Akins et al [17] reported on 3 cases of cerebral venous sinus thrombosis causing subdural hematoma and found 6 further cases published in the literature. It is possible that the etiology of the cSDH could be slow bleeding from engorged congested cortical veins [17]. This could also help to explain the bilateral convexity distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases this has been reported in adults with severe underlying illnesses [24][25][26][27][28]. Newborn infants are known to be more susceptible to venous sinus thrombosis and often are found to have coexisting subdural hematoma, as well [29].…”
Section: Theory: Unexplained Subdural Hematomas In Infants Can Be Thementioning
confidence: 95%